2021
DOI: 10.1080/10717544.2021.1905749
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antitumor effects of lupeol-loaded galactosylated liposomes

Abstract: Lupeol liposomes, modified with Gal-PEG-DSPE, were developed following a thin-film dispersion method. Then, the morphology, physicochemical properties, and in vitro release properties of those liposomes were investigated. The scanning electron microscopic images showed that most of the liposomes were spherical particles; they were similar in size and uniformly dispersed. Both lupeol liposomes and Gal-lupeol liposomes exhibited an average particle size of about 100 nm. The encapsulation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This leads to higher cellular uptake of galactose conjugated nanocarriers and subsequent drug delivery of encapsulated cargos in hepatocellular carcinoma. Zhang et al (2021), demonstrated the successful uptake of lupeol-loaded galactosylated liposomes by HepG2 cells, followed by efficacious in vitro and in vivo antitumor effects in the HCC xenograft model (Zhang et al, 2021). As previously shown by Nair et al (2019), gemcitabine-loaded galactosylated chitosan nanoparticles resulted in liver tumor-specific delivery and enhanced the anti-HCC efficacy of gemcitabine in vivo (Nair et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This leads to higher cellular uptake of galactose conjugated nanocarriers and subsequent drug delivery of encapsulated cargos in hepatocellular carcinoma. Zhang et al (2021), demonstrated the successful uptake of lupeol-loaded galactosylated liposomes by HepG2 cells, followed by efficacious in vitro and in vivo antitumor effects in the HCC xenograft model (Zhang et al, 2021). As previously shown by Nair et al (2019), gemcitabine-loaded galactosylated chitosan nanoparticles resulted in liver tumor-specific delivery and enhanced the anti-HCC efficacy of gemcitabine in vivo (Nair et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
“…This leads to higher cellular uptake of galactose conjugated nanocarriers and subsequent drug delivery of encapsulated cargos in hepatocellular carcinoma. Zhang et al. (2021) , demonstrated the successful uptake of lupeol-loaded galactosylated liposomes by HepG2 cells, followed by efficacious in vitro and in vivo antitumor effects in the HCC xenograft model ( Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo tests on wild-type FVB/N mice emphasized the liver-targeted delivery of GAL-L; as a result, the liver index as well as the liver weight of the respective treated mice displayed lower values compared to the non-targeted group. Histopathological analysis revealed that the GAL-L-treated mice had a clearer liver lobular structure with more obvious vacuoles and more abundant cytoplasm; in addition, liver cancer markers such as AFP, GPC3, and EpCAM mRNA exhibited lower expression levels compared to non-targeted lupeol-loaded liposomes [289].…”
Section: Lupeolmentioning
confidence: 92%
“…Recently, researchers have focused on tumor-targeted liposomal delivery system. Lactoferrin, 20 galactose 21 and glycyrrhetinic acid, 22 , 23 and so on were used to modify liposomes to target drugs into the tumor tissue more effectively. Estrogen receptors belong to the nuclear receptor protein family 24 involved in various physiological processes such as cell growth, reproduction, development, and differentiation.…”
Section: Introductionmentioning
confidence: 99%